Surviving in a Provisional Workplace: Foreign Lecturers’ Practices in an Asian HEI - Sipe, Marlon; Lemana, Henry; Saludadez, Jean (Journal of Education Culture and Society, 2024)
Aim. Drawing upon the foundational principles of the ethnomethodological perspective, the present study delves into the viewpoints of English as a foreign language (EFL) lecturer concerning teaching as a discipline and their corresponding teaching practices within the context of a provisional workplace in an Asian university. Methods. Five conveniently and purposively sampled participants were subjected to in-depth interviews to seek answers to the following research questions: (a) What are the views of the participants on their temporary appointments as EFL lecturers? (b) How do these views define their teaching practices in the classroom to survive in a provisional environment? The analysis brings to the surface recurring themes and patterns, providing valuable insights into how the participants survived in an academic environment that gave them non-executive positions. Results. Results indicated a multiplicity of views on their temporary appointments as EFL lecturers: Temporary appointments as a policy and student-centered position, a venue for professional standards, and a venue for career advancement. These views prompted them to blend with the local culture and accordingly to perform culturally appropriate teaching practices. Conclusion. It can be concluded that fostering cultural awareness, building strong interpersonal relationships, and pursuing continuous professional development are essential components for EFL teachers to excel in their roles. Additionally, institutions and stakeholders play a crucial role in creating an environment that acknowledges and bolsters the significant contributions of temporary EFL lecturers, thereby enabling them to make a lasting and positive impact within the academic community. Additional implications are discussed.